Trzynaste doroczne spotkanie Towarzystwa Badań Wczesnochrześcijańskich Azji i Pacyfiku (Singapur, 7-9.09.2023) - Wysocki, Marcin (Vox Patrum, 2023)
Report from the 13th Annual Meeting of Asia-Pacific Early Christian Studies Society which took place in Singapour on September 7-9, 2023.